2019
DOI: 10.7717/peerj.6171
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of straw and straw-derived biochar on soil aggregation and fungal community in a rice–wheat rotation system

Abstract: BackgroundSoil aggregation is fundamental for soil functioning and agricultural productivity. Aggregate formation depends on microbial activity influencing the production of exudates and hyphae, which in turn act as binding materials. Fungi are also important for improving soil quality and promoting plant growth in a symbiotic manner. There is a scarcity of findings comparing the long-term impacts of different yearly double-crop straw return modes (e.g., straw return to the field and straw-derived biochar retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 43 publications
(63 reference statements)
2
30
0
Order By: Relevance
“…It has been shown that soil fungal richness and diversity indices were signi cantly reduced after charcoal-based fertilization, which may be related to the different pathways of soil microorganisms to decompose soil organic matter. Biochar application can not only affect soil fungal community diversity, but also improve the fungal community structure and reduce the species with pathogenic potential, which in turn can lead to the development of soil fungi towards bene cial ora (Bai et al, 2019). In the present study, application of lees biochar signi cantly reduced the relative abundance of Fusarium and increased the relative abundance of Mortierella, which is similar to the results of a previous study (Yao et al, 2017).…”
Section: Effect Of Biochar On Soil Nutrient Effectivenesssupporting
confidence: 90%
See 1 more Smart Citation
“…It has been shown that soil fungal richness and diversity indices were signi cantly reduced after charcoal-based fertilization, which may be related to the different pathways of soil microorganisms to decompose soil organic matter. Biochar application can not only affect soil fungal community diversity, but also improve the fungal community structure and reduce the species with pathogenic potential, which in turn can lead to the development of soil fungi towards bene cial ora (Bai et al, 2019). In the present study, application of lees biochar signi cantly reduced the relative abundance of Fusarium and increased the relative abundance of Mortierella, which is similar to the results of a previous study (Yao et al, 2017).…”
Section: Effect Of Biochar On Soil Nutrient Effectivenesssupporting
confidence: 90%
“…The dry-land yellow soil in Guizhou has more than 4.6 million ha 2 , accounting for about 46% of the dry land area in the province (Guo et al, 2019;Luo et al, 2020). Yellow soil is not only sticky in texture and strong in acidity, and due to the shallow soil layer, soil nutrient leaching is also very easy to occur.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already reported that organic amendment exhibited beneficial effects on microbial biomass, activity, and community structure of the soil 1,37 . The variation of the predominant top 10 genera in specific aggregate classes was noted in Tables S2 and S3; these preferences could strongly contribute to the spatial heterogeneity and bacterial diversity found in soils.…”
Section: Discussionmentioning
confidence: 89%
“…OTUs were clustered using UPARSE software (UPARSE v7.0.1001, http://drive5.com/uparse/) (97% similarity) and analyzed against the SILVA database. PCR product purification, library construction, and data processing and analysis were conducted as described previously 37 . Sequences (raw reads) have been deposited into the NCBI Sequence Read Archive (SRA) database (Accession Number: SRP148725).…”
Section: Methodsmentioning
confidence: 99%
“…This may be because biochar can adsorb and fix a variety of inorganic ions and polar or non-polar organic compounds, and then form organic-inorganic composites and large-size aggregates in soil due to its porous structure and large specific surface area [21]. In addition, biochar can produce organic matter such as polysaccharides and proteins by decomposition, and also produces more secretions due to increase of microbial activity in soil, thereby promotes the formation of soil large aggregates [22]. However, Dong et al [6] found that the degree of soil aggregation in sandy loam had no significant change after three years of biochar application, possibly because of the difference in soil types.…”
Section: Effect Of Biochar and Nitrogen Fertilizer On Content And Dismentioning
confidence: 99%